Numerical Study of Liquid Metal Turbulent Heat Transfer in Cross-Flow Tube Banks - Alessandro Tassone; Jasper Meeusen; Andrea Serafini; Gianfranco Caruso (Energies, 2022)
Heavy liquid metals (HLM) are attractive coolants for nuclear fission and fusion applications due to their excellent thermal properties. In these reactors, a high coolant flow rate must be processed in compact heat exchangers, and as such, it may be convenient to have the HLM flowing on the shell side of a helical coil steam generator. Technical knowledge about HLM turbulent heat transfer in cross-flow tube bundles is rather limited, and this paper aims to investigate the suitability of Reynolds Average Navier–Stokes (RANS) models for the simulation of this problem. Staggered and in-line finite tube bundles are considered for compact (<semantics>a=1.25</semantics>), medium (<semantics>a=1.45</semantics>), and wide (<semantics>a=1.65</semantics>) pitch ratios. The lead bismuth eutectic alloy with <semantics>Pr=2.21×10−2</semantics> is considered as the working fluid. A 2D computational domain is used relying on the <semantics>k−ω</semantics> Shear Stress Transport (SST) for the turbulent momentum flux and the <semantics>Prt</semantics> concept for the turbulent heat flux prediction. The effect of uniform and spatially varying <semantics>Prt</semantics> assumptions has been investigated. For the in-line bundle, unsteady <semantics>k−ω</semantics> SST/<semantics>Prt=0.85</semantics> has been found to significantly underpredict the integral heat transfer with regard to theory, featuring a good to acceptable agreement for wide bundles and <semantics>Pe≥1150</semantics>. For the staggered tube bank, steady <semantics>k−ω</semantics> SST and a spatially varying <semantics>Prt</semantics> has been the best modeling strategy featuring a good to excellent agreement for medium and wide bundles. A poor agreement for compact bundles has been observed for all the models considered.